2006
DOI: 10.2174/138955706777435751
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal Plants as Potential Sources of Lead Compounds with Anti-Platelet and Anti-Coagulant Activ

Abstract: Medicinal plants are potential sources of lead compounds which can be further developed or optimised into novel therapeutics. This paper gives an overview of drug discovery from plants and an up-to-date and comprehensive review of plants and phytoconstituents reported to have anti-platelet and anti-coagulant activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 46 publications
0
9
0
1
Order By: Relevance
“…Much research has shown the importance of antithrombotic effect of polyphenol-rich plant extracts (Chua and Koh, 2006). In our previous in vitro studies, we found that incubation with polyphenol-rich extracts from chokeberry and grape seeds resulted in the changes of coagulation properties of human plasma (Bijak et al ., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Much research has shown the importance of antithrombotic effect of polyphenol-rich plant extracts (Chua and Koh, 2006). In our previous in vitro studies, we found that incubation with polyphenol-rich extracts from chokeberry and grape seeds resulted in the changes of coagulation properties of human plasma (Bijak et al ., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Although there are already osteoporosis medications and therapies, natural products still hold potential for treating osteoporosis, due to its higher acceptance by consumers. Fruit extracts is a major form of natural products, and a valuable and barely explored reservoir for plenty of disorders (Shen et al., ), including cancers (Chua & Koh, ; Greenwell & Rahman, ; Lampronti et al., ). Pepino ( Solanum muricatum , SM) is an evergreen plant native to South America (Huyskens‐Keil, Prono‐Widayat, Lüdders, & Schreiner, ), and is of close evolutionary relationship with tomato and eggplant.…”
Section: Introductionmentioning
confidence: 99%
“…Fruit extracts is a major N. Wang and L. Wang contributed equally to this work. form of natural products, and a valuable and barely explored reservoir for plenty of disorders (Shen et al, 2012), including cancers (Chua & Koh, 2006;Greenwell & Rahman, 2015;Lampronti et al, 2006). Pepino (Solanum muricatum, SM) is an evergreen plant native to South America (Huyskens-Keil, Prono-Widayat, Lüdders, & Schreiner, 2006), and is of close evolutionary relationship with tomato and eggplant.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, researchers are at the challenging task to identify a novel anticoagulant agents with more therapeutic effects and without side effects. Hence, at present, lavish focus is being carried out on plant material to acts as a potent source for this kind of research 15,16 . Since there is a compelling scientific evidences that consumption of dietary anticoagulants with anti-coagulant properties reduces the risks of thrombotic disorders 17,18 .…”
Section: Introductionmentioning
confidence: 99%